Decision Making: Alternatives to Rational Choice ModelsDecision Making: Alternatives to Rational Choice Models, by ZeyMary. Newbury Park, CA: Sage, 1992, 454 pp., $19.95, ISBN: 0-8039-4751-8. - Liang, Neng (Academy of Management Review, 1994)
The article reviews the book ?Decision Making: Alternatives to Rational Choice Models,? edited by Mary Zey.